Case report: Cavernous hemangioma in the right frontoparietal junction - Cao, Xuemin; chen, xiaoshuai; wang, yi; feng, shangang; wang, zengwu (Frontiers in Surgery, 2022)
Background Primary intraosseous cavernous hemangioma is a benign tumor with slow growth and is rarely seen in clinics. The clinical manifestations of most patients are progressive enlargement of the head mass. Case presentation We report a 30-year-old female patient with cavernous hemangioma at the frontoparietal junction. Upon admission, the right frontal lobe mass was progressively enlarged for 3 years and underwent lesion resection and stage I skull reconstruction. The postoperative outcome was good, with no recurrence at 1-year follow-up. Conclusion Primary intraosseous cavernous hemangioma is a relatively rare clinical tumor, the pathogenesis of which is still unclear, and most of them have no specific clinical manifestations. Characteristic imaging findings are highly suspicious of this disease, but the definitive diagnosis still depends on histopathological examination. Currently, total surgical resection of the tumor is a relatively effective and preferred treatment.